Ethnopedology: Popular and scientific classification of a soil profile in the quilombola community Os Rufinos, Pombal-Paraíba - Almeida, Rodolfo Trigueiro de; Dantas, Jussara Silva; Regis, Jefferson Luan de Araújo; Costa, Leonardo José Silva da; Santos, Tiago Silva; Ventura, Rosy Carina de Araújo; Silva, Francisco Alves da (Seven Editora, 2024)
The culture of a people is measured by what it produces as a manifestation, material or immaterial, of its daily expressions, whether symbolic, discursive or in the spectrum of a domestic economy that has its essence founded as a mold of expression of the culture and identity of the place. Thus, in this work we seek to understand the form of soil classification according to the use and destination of this soil for the production of ceramics in the Quilombola Community the Rufinos in the municipality of Pombal-PB. The study of local soil names can contribute to the advancement of formal knowledge, as well as to the development of socially appropriate management strategies. If a quilombola names some soils based on the characteristics of the arable layer, this does not mean that he or she is necessarily unaware of what is below this layer. Ethnopedology enables the dialogue between popular knowledge and technical scientific knowledge, debating the connection of knowledge between what we already know and what we can still learn. Popular knowledge originates from the personal experience of each individual, transmitted from one generation to another, through facts, stories and arguments, through daily contact with variations in climate, vegetation and soil. Seeking to understand natural resources from a less technical point of view, but sufficient for the development of its activities. Thus, in this work, it was possible to describe a soil profile according to the conditions of use of the community and also according to the scientific society. DOI:https://doi.org/10.56238/sevened2024.010-069